Foucault with Lacan, the Subject in Action - Mendelsohn, Sophie (Filozofski vestnik, 2011)
The critique of psychoanalysis by late Foucault discretely opens up the possibility of a paradoxical dialogue with Lacan. The article aims to reconstruct the possibility of such a dialogue by recasting the issue of the subject. Conceiving the latter as an effect of his act, the article sets out from a “praxeology” which aims to establish the relationship between the subject and truth by other means than those provided by knowledge, in order to challenge the ‘rights’ of epistemology. What kind of strategies are required for building such a relationship; what kind of aesthetical and ethical consequences might follow from such a departure point? To answer these questions, the virtual dialog of Foucault and Lacan, presented here, confronts “parrhesia” and “sinthome”, two concepts which help us shed some light on their common problematics. Far from indulging in vain polemics, yet without ignoring the irreducible differences, the aim of the article is to examine how Foucaldian notions can support the renewal of the fundamental concepts of psychoanalysis – such as the symptom – and how a Lacanian orientation can further open up Foucault’s inquiry into subjectivity.